Standar Proses dan Inovasi Pembelajaran Geografi dalam Kurikulum 2013 Sebagai Salah Satu Dasar Menjadikan Anak Bangsa yang Bermartabat - Rahmayoni Rahmayoni; Syafwi Anwar; Nola Aprilia Sukhaimi; Khairani Khairani (Journal on Education, 2022)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed by themselves, society, nation and state. Characteristics of objects of geographic study there are concrete and some are in the form of "abstract", because geography studies the distribution, interaction, interrelation, interdependence, and various processes that work in space on a large scale. The context of the 2013 Curriculum implementation, teachers, including Geography teachers, as the spearhead in the development and implementation of geography learning at the school level, should understand the position of Geography itself in the K-13 Structure. Furthermore, teachers have the responsibility and obligation to make basic efforts in various forms of learning innovation so that the implementation of the learning process can achieve the specified competencies, while at the same time taking part in bringing the children of this nation to become a dignified nation in the eyes of the nation and internationally.